Ciprofloxacin prophylaxis during autologous stem cell transplantation for multiple myeloma in patients with a high rate of fluoroquinolone-resistant gram-negative bacteria colonization - Zavrelova, Alzbeta; Paterova, Pavla; Gabalec, Filip; Zak, Pavel; Radocha, Jakub (Biomedical papers, 2019)
Background: Ciprofloxacin prophylaxis used to be a standard precaution during autologous stem cell transplantation. Its benefit, with a high prevalence of fluoroqinolone resistance in the population, has recently been under scrutiny. Objective: To evaluate the impact of cessation of ciprofloxacin prophylaxis during stem cell transplantation for multiple myeloma. Patients and Methods: Data from 104 patients with multiple myeloma transplanted during the period from January 2013 to April 2015 were retrospectively reviewed. 67 received standard ciprofloxacin prophylaxis (group A) and 37 received no antibacterial prophylaxis (group B). Results: Febrile episodes during neutropenia, bloodstream infection (BSI) and mortality in these two cohorts were evaluated. Gram negative BSI was assessed for the colonization of quinolone-resistant gram-negative pathogens. Secondary Clostridium difficile enterocolitis presence was determined in both cohorts. There were 42 (63%), 7 (10%), and 0 febrile episodes, BSI and gram-negative BSI respectively in group A, and 34 (92%), 12 (32%), and 4 (11%) respectively in group B. The differences in the number of febrile episodes (P=0.0011) and deaths (P=0.0427) were statistically significance. Mortality was 0 and 3 (8%) in group A and group B, respectively. There was no significant difference in colonization with quinolone-resistant gram negative pathogens (25 (37%) versus 11 (30%)) between groups. The occurrence of Clostridium difficile colitis was the same in both groups. Conclusion: We resumed ciprofloxacin prophylaxis for the following reasons. There was a significant reduction in febrile episodes, and consequently a sparing effect of antibiotics used for treatment of this condition. No difference in Clostridium difficile colitis occurred and the mortality rate of 8% in group B was unacceptably high.
Keywords: neutropenia; autologous transplantation; multiple myeloma; ciprofloxacin prophylaxis